Numerical distance effect in patients with schizophrenia. (23rd March 2016) - Pourrahimi, Ali Mohammad; Mazhari, Shahrzad; Shabani, Mohammad; Tabrizi, Yousef Moghadas; Sheibani, Vahid
Highlights: Patients with schizophrenia exhibited the standard distance effect. Access to the mental number line is preserved in patients with schizophrenia. Automatic numerical processing is intact in patients with schizophrenia. Abstract: There is growing evidence showing that mental representation of numbers is impaired in patients with schizophrenia. Yet, no study has examined the distance effect in the patients. We assessed the distance effect using two number size comparison tasks, with different number references (5 and 7) in 23 patients and 28 healthy individuals. Response times and error rates significantly increased when the distances between the centered references and the targets decreased in both groups. However, patients responded significantly slower and had more error rates compared to controls. Our finding indicates distance effect in patients is similar to the controls, indicating an automatic numerical processing is preserved in patients with schizophrenia.